Physicochemical variability in Brazilian guava accessions grafted onto a nematode resistant rootstock - Santos-Lourenço, Andressa Mirelle; Fernandes-Santos, Carlos Antônio; Tonetto de Freitas, Sérgio; Mattos da Silva, Danillo Olegario (Revista Mexicana de Ciencias Agrícolas, 2024)
Guava is a fruit species of worldwide importance due to its characteristics favorable for consumption; for example, aroma, flavor, texture and vitamin C. This study aimed to characterize the physicochemical variability of Brazilian guava accessions grafted onto BRS Guaraçá, a nematode resistant rootstock, to guide the development of new cultivars. Fruits from 87 accessions from the Embrapa Semiárido Psidium Germplasm Bank, sampled in 12 Brazilian States and established at Petrolina, PE, Brazil, were analyzed in 2020 for peel and pulp color, pulp firmness, titratable acidity, soluble solids, vitamin C, lycopene, and β-carotene in the fresh pulp. The data were subjected to analysis of variance and histograms construction. The results were significant (p< 0.05) for all quantitative variables, indicating phenotypical variability among accessions. The β-carotene contents ranged from 0.02 to 1.83 mg.100 g-1, with a mean of 0.49 mg 100 g-1. The lycopene mean value was 0.77 mg100 g-1, ranging from 0 to 3.7 mg 100 g-1. Accessions GUA33PE and GUA135RR showed high pulp firmness values and are recommended for the development of cultivars with greater resistance to transport. Accessions GUA31PI, with 686 mg 100 g-1 and GUA48SE, with 621 mg 100 g-1, showed high values of vitamin C and are recommended for the development of cultivars with higher contents of this bioactive compound.